2022
DOI: 10.1007/s11517-022-02630-z
|View full text |Cite
|
Sign up to set email alerts
|

GA-MADRID: design and validation of a machine learning tool for the diagnosis of Alzheimer’s disease and frontotemporal dementia using genetic algorithms

Abstract: Artificial Intelligence aids early diagnosis and development of new treatments, which is key to slow down the progress of the diseases, which to date have no cure. The patients’ evaluation is carried out through diagnostic techniques such as clinical assessments neuroimaging techniques, which provide high-dimensionality data. In this work, a computational tool is presented that deals with the data provided by the clinical diagnostic techniques. This is a Python-based framework implemented with a modular design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…By combining an interpretable graph neural network with the dataset collected from ADNI, Mansu et al [122] bridge the gap between efficiently integrating longitudinal neuroimaging data and biologically meaningful structure and knowledge to develop precise and understandable systems. Fernando et al [155] presents a Python-based computational tool to deal with the data obtained during clinical diagnosis. The tool integrates data processing, designing predictive models and features of XAI for explainability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By combining an interpretable graph neural network with the dataset collected from ADNI, Mansu et al [122] bridge the gap between efficiently integrating longitudinal neuroimaging data and biologically meaningful structure and knowledge to develop precise and understandable systems. Fernando et al [155] presents a Python-based computational tool to deal with the data obtained during clinical diagnosis. The tool integrates data processing, designing predictive models and features of XAI for explainability.…”
Section: Resultsmentioning
confidence: 99%
“…The suggested strategy addresses the problem of ongoing remote monitoring of elderly individuals to aid in the early identification of cognitive decline and to better assist clinicians in reaching a diagnosis. In another study, Fernando et al [155] proposed a diagnostic tool that uses a decision tree that provides a simple and unambiguous set of decision rules to provide capabilities to clinicians to give insights into the pathophysiology of AD and behavioural Fronto Temporal Dementia (bvFTD). This paper is beneficial for early detection and diagnosis in the medical field because it outlines all the processes needed to evaluate the datasets, including data preparation, selection of features using an evolutionary approach, and in the creation of a model for the disease discussed in the paper.…”
Section: Rule-basedmentioning
confidence: 99%
“…A third issue is that existing DL-assisted diagnostic studies are still reliant on expert-level preprocessing based on hypotheses. Some ML tools help to distinguish the AD and FTD symptoms with genetic algorithms [ 70 ]. It has been demonstrated that a data-centric perspective helps to understand AD and FTD disorders by allowing the results to be interpreted.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several Bayesian models proposed that were not causal BN models 22 including naïve Bayes models 23 . Recently García-Gutierrez et al proposed a two-layered model for the diagnosis of AD and Frontotemporal Dementia (FTD) 24 . The first layer executes binary classification using SVMs.…”
Section: Related Ai Approaches Alzheimer's Diseasementioning
confidence: 99%